THE EFFECT OF ACROSTIC TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Rafika Azmi; Indra Hartoyo (Universitas Negeri Medan, 2015)
This research aimed to finding out whether students’ achievement taught by usingAcrostic Technique has significant effect than that was taught by GroupInvestigation Method in Writing Descriptive Text. The research was conducted byExperimental research using two groups. They are Experimental groupthat usedAcrostic Technique and Control group that used Group Discussion Method. Thepopulation of this research was the tenth grade students of SMA Swasta KesumaBangsa Londut. There were three parallel classes which consist of 30 students foreach class. The data was taken from writing test. After analyzing the data, it wasfound that the value of tobserved was 4.511 with degree of freedom (df) 28 at thelevel of significance p (0.05) = 2.048. It means that tobserved (4.511) is higher thanttable (2.048). It was found that students’ achievement in Writing Descriptive Texttaught by Acrostic Technique has significant effect.